ANALISIS ISU DAN KEBIJAKAN PEMBANGUNAN BERPERSPEKTIF GENDER KABUPATEN BANJARNEGARA - SOFA MARWAH (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Human Development Index (HDI) and Gender DevelopmentIndex (GDI) of regencies show disparity with the achievements ofthe national and provincial levels. One of which is the HDI and GDI ofBanjarnegara Regency, which is lower than Central Java Province,even the third-lowest among regencies in Central Java. IN addition,the disparity between HDI and GDI shows that the development resultshave not been accessed by both men and women fairly and equally. Theproblem of gender development in Banjarnegara Regency is reflectedin the low level of participation of school-aged children both male andfemale, the high rate of maternal mortality, the low absorption of womenjob seekers in employment, violence against women, the lack of womenpolitical representation, and so forth. In connection with these conditions,Banjarnegara regency has spawned the policies of gender responsive localdevelopment strategies as a form of commitment and hard work of localgovernments to resolve the issue of gender in the area. The commitmentand efforts of local government deserves appreciation.